2003
DOI: 10.1034/j.1601-0825.2003.00955.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection in Thai patients with oral lichen planus

Abstract: The present study reports a small, but statistically significant high prevalence of HCV infection among patients with OLP, although the underlying mechanism still remains unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 52 publications
2
40
2
Order By: Relevance
“…The first report of a possible relation between HCV and OLP was established in 1991 by Mokin et al, [15]. In the present study all the patients were found to be seronegative to anti HCV antibody thus contradicting the report of an association between OLP and HCV.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The first report of a possible relation between HCV and OLP was established in 1991 by Mokin et al, [15]. In the present study all the patients were found to be seronegative to anti HCV antibody thus contradicting the report of an association between OLP and HCV.…”
Section: Discussioncontrasting
confidence: 56%
“…Till date there have been many published reports which have proposed the possible association between OLP and chronic liver disease such as that with primary biliary cirrhosis and with chronic active hepatitis [15].…”
Section: Discussionmentioning
confidence: 99%
“…As they point out, OLP has been associated with a number of systemic disorders, generally of autoimmune origin (myasthenia gravis, Sjögren's syndrome, ulcerative colitis, psoriasis, celiac disease, some liver diseases, thymoma, and lupus erythematosus); however, only in a few conditions has this link been confirmed. [2][3][4][5][6] For example, the correlation between chronic hepatitis C virus (HCV) infection and OLP would be one of these, even if many contrasting results have been published, [7][8][9][10][11][12][13][14] and the partial dependency on geographic factors as well as genetic differences has been focused. 15,16 Furthermore, autoimmune conditions, such as systemic lupus erythematosus, rheumatoid arthritis, and celiac disease have also been simply found to be associated with autoimmune thyroid diseases, 17 but without great and definitive evidence.…”
Section: Association Of Oral Lichen Planus With Thyroid Disease In a mentioning
confidence: 99%
“…[15] have demonstrated that HCV infects keratinocytes from cutaneous LP lesions and that the viral RNA is translated in these cells as demonstrated by the HCV incorporated in the skin biopsies. Klanrit et al [16] showed a small but significant percentage of HCV infected patients with OLP. The study of Harman et al [11] supported the view that the consistency of HCV and OLP is probably more than coincidental and they recommend that it is appropriate to screen all patients with LP for HCV infection.…”
Section: Discussionmentioning
confidence: 99%